Cement composition and method for producing cement component
By reasonably preparing refractory raw materials and additives in refractory concrete compositions to ensure uniform distribution of components, the safety risk of aluminum metal powder and water reaction and low thermal bending strength in the prior art are solved, and the production of high-strength and dimensionally stable refractory concrete components are achieved.
Patent Information
- Application Number
- CN202380066049.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-16
- Filing Date
- 2023-08-14
- Publication Date
- 2025-04-29
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
There are safety risks in the fire process of existing refractory concrete compositions, especially when using aluminum metal powder, it is easy to react with water to form hydrogen, resulting in high explosion risk and low thermal bending strength, making it difficult to produce high-strength, dimensionally stable concrete components.
A refractory concrete composition is employed that includes 35 to 70% of the coarse part of the refractory raw material having a particle size of at least 0.5 mm, 15 to 30% of the fine part of the refractory raw material having a particle size of less than 0.5 mm, 0 to 20% of the fine calcined alumina, 0 to 2% of the fine magnesium oxide powder, 2 to 7% of the fine aluminum metal powder, 2 to 8% of the fine carbon support and 4 to 20% of the aqueous colloidal silica sol suspension to ensure uniform distribution of the ingredients and form a high-strength ceramic phase during the firing process.
The composition can be safely processed with aqueous liquid during firing, avoiding the risk of explosion, and the produced concrete members have significantly improved thermal bending strength and dimensional stability, and are suitable for refractory applications.
Smart Images

Figure CN119907784A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a refractory concrete composition. Furthermore, the present invention relates to a concrete element produced from the refractory concrete composition and to a method for producing a fired concrete element. Background Art
[0002] In the prior art of refractory products, it is known that there are many formulas for producing refractory linings. For carbon-containing refractory products, it is known to use so-called antioxidants in the mixture, for example in the form of metal powders. These additives have the advantage of protecting carbon from oxidation by forming bulky metal oxides at higher temperatures and low oxygen supply, which reduces the pore space of the refractory product. However, if the mixture or the resulting material (mass) contains a water phase, these metal powders cannot be used as antioxidants, or can only be used to a limited extent. In this case, due to the reactivity of the metal powder with water and the formation of related hydrogen, there is a risk of explosion, so the safety risk is very high. Among the categories of metal powders, aluminum metal powders are particularly highly reactive. Therefore, when using reactive aluminum metal powders, it is necessary to avoid contact with water or moisture, because a large amount of hydrogen can be formed, which brings high safety risks due to the risk of explosion. In contrast, for example, silicon metal powders show much lower reactivity when in contact with water, and are therefore less critical when handled.
[0003] For example, from US Pat. No. 8,450,229 B2 a mixture for producing a carbon-bonded magnesium block, i.e. a basic refractory block, which can be used, for example, in converters, is known, wherein the mixture comprises, as main component, magnesium oxide as refractory rock raw material, as well as pyrogenically prepared silicon dioxide powder, at least one synthetic resin as binder and at least one metal-based powdered antioxidant, and wherein the proportion of silicon dioxide powder is between 0.01 and 5% by weight, based on the proportion of magnesium oxide. Here, the pyrogenic silicon dioxide powder is present in the form of an organic dispersion, for example in alcohol, in order to avoid the above-mentioned problems of contact of metal powders with water.
[0004] In general, US 8,450,229 B2 recommends operating under anhydrous conditions as far as possible. It should therefore be pointed out that during the firing of carbon-containing refractory blocks containing metallic antioxidants, in particular aluminum metal, carbide phases may form. This is why, in applications where the mold can cool to a large extent after in-situ carbonization and then absorb water, as may occur, for example, during production interruptions, this can lead to the decomposition of the carbides formed during carbonization with accompanying changes in volume and thus to the destruction of the molded body.
[0005] Furthermore, for example, from US 2012 / 0142518 A1 a cement-free refractory composition is known, wherein the composition comprises aluminum oxide, silicon carbide, dry pyrogenic silica, aluminum metal, carbonaceous material, reactive aluminum oxide, and in addition an antioxidant in the form of boron carbide, silicon or a mixture thereof. When US 2012 / 0142518 A1 mentions pyrogenic silica as a component of the refractory composition, it is explicitly intended to use dry pyrolytically prepared silica particles with a particle size in the micrometer range (so-called "microsilica" particles), rather than colloidal silica. The proportion of aluminum metal powder in the refractory composition is specified to be up to 1.5% by weight, preferably up to 1% by weight, wherein, due to the necessity of containing pyrogenic silica in the composition, the refractory composition can optionally even be prepared without the addition of aluminum metal powder. If aluminum metal is used to produce the refractory composition, it is recommended to add aluminum metal powder having a particle size of about 200 μm, because otherwise the reaction kinetics in the refractory composition will be difficult to control when using fine-grained metal powders with a smaller particle size below 200 μm, especially in the presence of water.
[0006] As further proposed in US2012 / 0142518 A1, the formulations of the refractory composition proposed in US2012 / 0142518 A1 using dry fumed silica (see formulations "Mix 1" and "Mix 2" in Table II and Table III) were both tested and compared with formulations in which an aqueous suspension of colloidal silica was used instead of fumed silica (see formulations "Mix 3" and "Mix 4" in Table II and Table III). In these formulations, water was added in corresponding proportions when dry fumed silica was used.
[0007] Comparison of fired blocks produced using different formulations shows that the hot flexural strength (Hot MOR, Hot Modulus of Rupture; measured according to ASTM C583 method) obtained by testing the refractory compositions proposed in US2012 / 0142518 A1 using dry fumed silica (formulations "Mix 4" and "Mix 2") is about twice that of the corresponding comparative tests using a colloidal silica aqueous suspension instead of fumed silica (formulations "Mix 3" and "Mix 1") when measured at a temperature of 2700°F (equivalent to approximately 1500°C). For the refractory composition proposed in US2012 / 0142518 A1 (see Tables II and III: formulation "Mix 1"; with 0.5% by weight of aluminum metal powder and 6% by weight of fumed silica in the form of "microsilica" particles), a value of 742 psi (pounds per square inch) was obtained as the maximum value of the hot flexural strength at 2700°F (i.e. about 1500°C), which corresponds to a value of about 51 bar or 5.1 MPa, respectively. In the corresponding comparative test (see Tables II and III: formulation "Mix 3"; with 0.5% by weight of aluminum metal powder and 8% by weight of aqueous suspension of colloidal silica), under the same other test conditions, an aqueous suspension of colloidal silica was used instead of fumed silica, and a value of only 366 psi was obtained for the hot flexural strength at 2700°F, which corresponds to about 25 bar or 2.5 MPa, respectively. From US 2012 / 0142518 A1 it follows that, regardless of whether aluminum metal powder is used or not, the use of silica particles in a colloidal silica sol suspension is in any case disadvantageous compared to the use of fumed silica in the form of “silica micropowder” particles.
[0008] A disadvantage of the refractory compositions known from US 2012 / 0142518 A1 (having the formulations “Mix 1” to “Mix 4”) is at least that the strength values obtained for fired shaped blocks produced with these compositions are relatively low.
[0009] Tables II and III also show another comparative test "Mix 5" with conventional cement-bonded concrete, which has a hot flexural strength of only 122 psi (equivalent to approximately 8.4 bar or 0.84 MPa, respectively) at 2700°F, and thus has significantly worse strength values than formulations "Mix 1" to "Mix 4". In this conventional concrete composition according to formulation "Mix 5", which contains a high proportion of 3.3% by weight of calcium aluminate cement, a small proportion of only 0.1% by weight of aluminum metal powder and 2.5% by weight of pyrogenically prepared silicon dioxide particles having a particle size in the micrometer range ("microsilica" particles), the addition of water (5% by weight of water according to "Mix 5") inevitably leads to an exothermic hydration reaction of the aluminum metal powder with water. However, in this reaction, hydrogen is disadvantageously formed (see also paragraph
[0046] of US 2012 / 0142518 A1), wherein the aluminum metal powder reacts to form aluminum oxide and is therefore no longer a reactant in the microstructure of the concrete composition. The addition of water to "Mix 5" will inevitably lead to the formation of hydrogen and oxygen gases if, for example, higher amounts of 1% by weight or more of aluminum metal powder are added, which is why the "Mix 5" recipe is not suitable for the safe production of high-strength, especially dimensionally stable, refractory concretes.
[0010] From KR 101 047 358 B1, refractory concrete compositions for the steel industry are known, in which anionic and cationic curing agents are used to achieve improved corrosion resistance of silica sol and high spray adhesion. The concrete compositions of exemplary embodiments 1 to 8 mentioned in both Table 1 and Table 2 of KR 101 047 358 B1 each employ a refractory starting material in the form of brown corundum (brown fused aluminum oxide), wherein the coarse particle proportion is 71% by weight to 79.5% by weight. There is no information on the fine particle proportion of refractory starting materials with a particle size of less than 0.5 mm. For example, in the formulations of exemplary embodiments 7 and 8, 5% by weight of carbon black, 5% by weight of aluminum metal powder with a particle size of about 0.2 mm and 7.4% by weight of silica sol with a proportion of 0.3% by weight of anionic dispersant are used. The disadvantage of these concrete compositions is at least that, due to the lack of fine-grained proportions, there is no binding matrix in which the coarse-grained components with a high coarse-grained proportion of up to 10 mm are embedded. In addition, the use of aluminum metal powder with a particle size of up to 0.2 mm is also disadvantageous, because such metal powders are less reactive due to their particle size, cause local concentration differences in the microstructure, and therefore cannot be distributed uniformly in the concrete composition like fine-grained aluminum metal powders with smaller particle sizes. The hot flexural strength (also called hot rupture modulus) of the concrete compositions detailed in the table was determined in each case at a temperature of 1400° C. and in the case of the formulation of exemplary embodiment 7 was a maximum of 77 kg / cm2 Or in exemplary embodiment 8, a maximum of 78 kg / cm 2 (Each equivalent to 7.6MPa), which is relatively low.
[0011] However, in most cases, the thermal rupture bending strength of such refractory products is given at 1500° C. (as in the case of US 2012 / 0142518 A1), where the skilled person can obtain the thermal rupture bending strength from, for example, It is known from the publication of J. et al.: "On the high temperature bending strength of castables" [Ceramics-Silikáty 56 (3) 198-203 (2012)] that the hot bending strength of refractory materials, in particular with a low cement content (ULCC, ultra-low cement castables) or without cement (NCC, cement-free castables), decreases with increasing firing temperature. It can therefore be assumed that the maximum hot bending strength at 1400° C. specified in KR 101 047 358 B1, when extrapolated at a temperature of 1500° C., is in any case less than 7.6 MPa and is therefore relatively low. Advantageously, the strength values specified in KR 101 047 358 B1, in particular the hot bending strength of fired shaped blocks prepared with the compositions according to exemplary embodiments 7 and 8, are relatively low.
[0012] CN 110 240 486B relates to a conventional cement-bound concrete mass having a significant proportion of calcium aluminate cement of at least 4 to 6% by weight, which contains, among other things, aluminum metal powder in a proportion of 4 to 6% by weight. As mentioned above, the aluminum powder added to the conventional cement-bound concrete mass, especially in larger amounts or higher concentrations, reacts very strongly with water and forms hydrogen, including the formation of hydrogen and oxygen gases. Therefore, the production method of the cement-bound concrete mass detailed in CN 110 240 486B aims to encapsulate the aluminum powder by a complex surface treatment and calcination process using ceramic membrane microcapsules, so that the metal material with an oxide surface inertized in this way does not react with water when added to the cement-bound concrete mass. In a first process step, the aluminum metal powder is inertized by forming surface aluminum oxide. In a second process step, the surface corroded aluminum metal powder is immersed in an alkaline silica sol. Finally, the surface-treated aluminum metal powder is calcined at 500 to 700° C., wherein, at a higher temperature of 1000° C., the oxide layers of aluminum oxide (Al2O3) and silicon dioxide (SiO2) form ceramic films in the form of mullite formed in situ. These ceramic films form microcapsules that surround the inner aluminum powder and inert it. The silicon dioxide particles in the silica sol are incorporated into the microcapsules. In summary, the cement-bound concrete material of CN 110 240 486B with a high cement content of at least 4% by weight is added neither fine-grained aluminum metal powder nor aqueous colloidal silica sol suspension, but microcapsules surrounded by ceramic films, in which the inert aluminum metal powder is encapsulated and silicon dioxide particles are incorporated.
[0013] In any case, the method described in CN 110 240 486 B has the disadvantage that the individual production of the ceramic microcapsules added to the cement-bound concrete mass is very complicated. The described in-situ formed mullite whiskers also have the disadvantage that in the presence of higher proportions of calcium aluminate cement, the in-situ formed mullite leads to a low-melting phase in the fired concrete element which reduces the hot strength properties. This is well known to the person skilled in the art.
[0014] In order to obtain high-strength, in particular dimensionally stable refractory concrete, corresponding concrete compositions should therefore be produced as far as possible without cement or contain a significantly lower proportion of cement binder than at least 4% by weight of calcium aluminate cement as specified in CN 110 240 486 B. Furthermore, the in situ formation of ceramic mullite phases must be avoided during the firing of such concrete components, and therefore high-strength, in particular dimensionally stable concrete components with high hot flexural strength should be as free as possible from in situ formed ceramic mullite phases.
[0015] From JP 2001 114571 A, a formulation for a castable refractory material for producing a refractory lining is known, in which 0.5 to 10% by weight of aluminum powder and amorphous silicon dioxide particles corresponding to a solids content of 0.1 to a maximum of 2% by weight are added to a concrete composition. The amorphous silicon dioxide particles are provided by an aqueous colloidal silica sol suspension with a solids content of 20% by weight of silicon dioxide particles. The addition of a higher proportion of an aqueous colloidal silica sol suspension (with 20% silicon dioxide particles) with a solids content of more than 2% by weight of amorphous silicon dioxide particles in the concrete composition is described as disadvantageous, since this reduces the corrosion resistance of the refractory material. No information is given in JP 2001 114571 A about the strength of the fired concrete element.
[0016] The disadvantage of the formulations known from JP 2001 114571 A is at least that the proportion of nanoscale silicon dioxide particles introduced into the corresponding concrete composition via the silica sol suspension is very low. With these formulations it is not possible to produce concrete components which are particularly dimensionally stable after firing.
[0017] Concrete compositions are also known from US 2014 / 0291904 A1 in which 0.1 to 5% by weight of pyrogenically prepared silicon dioxide particles (so-called "microsilica" particles) are used. Water is added as mixing fluid. In the concrete compositions, which can contain up to 0.5% by weight of cement binder, aluminum metal powder is deliberately absent in order to prevent the formation of hydrogen when mixing with water. US 2014 / 0291904 A1 does not mention the addition of a part of a colloidal silica sol suspension. However, with these formulations, it is not possible to produce concrete components that are particularly dimensionally stable after firing. Summary of the invention
[0018] The object of the present invention is therefore to improve the disadvantages known from the prior art and to provide a composition for producing high-strength, in particular dimensionally stable, carbon-containing refractory concrete, which has suitable metal powders, in particular aluminum metal powders, to prevent oxidation, wherein the composition can still be processed with aqueous liquids without safety risks, in order to produce concrete elements suitable for refractory applications with improved strength, in particular improved hot bending strength. In addition, a composition for producing refractory concrete should be provided, with which concrete elements can be produced and which are particularly dimensionally stable after firing. Another object of the present invention is to provide a method for producing such a fired concrete element. DETAILED DESCRIPTION
[0019] In order to solve the object of the present invention, a refractory concrete composition is provided, wherein the concrete composition comprises:
[0020] a coarse-grained fraction of at least one refractory raw material having a grain size of at least 0.5 mm, preferably having a grain size of 0.5 mm to 12 mm, in a proportion of 35 to 70%, preferably 50 to 65%, by weight;
[0021] - a fine-grained fraction of at least one refractory raw material having a grain size of less than 0.5 mm in a proportion of 15 to 30% by weight, preferably 20 to 25% by weight;
[0022] - wherein at least one refractory raw material is selected from the group consisting of sintered alumina, fine corundum, brown corundum, grey corundum, magnesia alumina spinel, mullite, bauxite, andalusite, refractory clay and / or silicon carbide, and mixtures thereof;
[0023] - fine-grained calcined aluminum oxide having a particle size of less than 0.1 mm, preferably having a particle size of less than 50 μm, in a proportion of 0 to 20%, preferably 1 to 7%, by weight;
[0024] - a fine-grained magnesium oxide powder having a particle size of less than 0.1 mm in a proportion of 0 to 2% by weight,
[0025] - a fine-grained aluminum metal powder having a particle size of less than 100 μm, preferably having a particle size of less than 63 μm, in a proportion of 2 to 7% by weight, preferably 3 to 6% by weight,
[0026] - a proportion of 2 to 8% by weight of at least one fine-grained carbon support having a particle size of less than 100 μm, wherein the at least one fine-grained carbon support comprises or is carbon black and / or graphite;
[0027] - an aqueous colloidal silica sol suspension in a proportion of 4 to 20% by weight, wherein the silica sol suspension contains amorphous nanoscale silicon dioxide particles in a solid content of 30 to 50% by weight.
[0028] In the refractory concrete composition according to the invention, the proportion of fine-grained components having a particle size of less than 0.5 mm, and in particular the fine-grained fraction of at least one refractory raw material, forms a bonding matrix for the coarse-grained fraction of at least one refractory raw material having a particle size of at least 0.5 mm and more. The granular coarse components having a particle size of at least 0.5 mm are embedded in the bonding matrix formed by the fine components, which is advantageous for the subsequent production of particularly dimensionally stable concrete components.
[0029] Surprisingly, it has been shown that the refractory concrete composition according to the invention, in contrast to the teaching of US 2012 / 0142518 A1, uses nanoscale silicon dioxide (SiO 2 ) particles present in an aqueous colloidal silica sol suspension, in combination with the other components of the refractory concrete composition according to the invention, for the production of particularly dimensionally stable, high-strength fired concrete components.
[0030] The term "silica sol" refers to an aqueous colloidal suspension of predominantly spherical polysilicic acid molecules, with 30% to a maximum of 60% silicon dioxide by weight. The term is composed of "silica" for silicic acid and the synonym "sol" for colloid. Here, roughly spherical polysilicic acid particles are linked by oxygen bridges to form amorphous silicic acid, which is also called silica gel.
[0031] Due to their relatively small particle size in the nanometer range, nano-sized silica (SiO2) particles can only be distributed in an insufficiently uniform manner in the rest of the concrete composition as dry anhydrous solid components (i.e. dry silica particles) in a material mixture with a uniformly larger particle size in the micrometer or millimeter range. In addition, the storage of the dry mixture for the production of refractory concrete compositions leads to the separation of the dry silica particles contained therein. However, in aqueous colloidal silica sol suspensions, the nano-sized silica particles are present in the advantageous form of uniformly distributed spherical individual particles, which are not cross-linked with each other and are hydroxylated on their surface.
[0032] Introducing a sufficient amount of aqueous colloidal silica sol suspension as a mixing fluid into the refractory concrete composition, optionally by mixing in a suitable concrete mixer, provides the benefit that, once the silica sol suspension uniformly wets the mixture of the concrete composition, the nano-scale silica particles are distributed as uniformly or evenly as possible in the refractory concrete composition, and the concrete composition is flowable and can be cast. It is thus ensured that, in particular after mixing the components of the refractory concrete composition, other fine-grained components such as fine-grained aluminum powder and fine-grained carbon carrier are distributed as uniformly or evenly as possible in the concrete composition. In the following, the term "uniformly distributed" is therefore understood to mean the most uniform distribution of fine-grained components, especially those with relatively small particle sizes on the nanometer or micrometer scale, in the mixture of the refractory concrete composition. The more uniformly or evenly the fine-grained components are distributed in the mixture of the refractory concrete composition with different particle sizes, the more uniform the properties of the concrete element prepared with the concrete composition according to the invention.
[0033] Without being bound by any theory, the interaction of the refractory concrete composition according to the present invention, in particular a sufficient amount of nanoscale silicon dioxide (SiO2) particles present as a silica sol, which is particularly reactive and particularly uniformly or evenly distributed in the refractory concrete composition in the form of an aqueous colloidal silica sol suspension, in combination with a sufficient amount of fine-grained aluminum metal powder and a sufficient proportion of a fine-grained carbon support having a particle size of less than 100 μm, appears to be particularly advantageous.
[0034] In our own preliminary tests, it was possible to show that when firing concrete elements produced from the concrete composition according to the invention, high-strength ceramic phases are formed in situ, which have a proportion of 2% by weight to 7% by weight of fine-grained aluminum metal powder with a particle size of less than 100 μm in the concrete composition, in combination with the other constituents of the concrete composition. Depending on the respective firing temperature, these ceramic phases contain aluminum in the form of one or more oxides, carbides, mixed carbides, oxycarbides, nitrides and / or oxynitrides, and / or corresponding mixtures thereof.
[0035] It can be shown that the in situ phase formation of an aluminum-based ceramic phase is favorably promoted by the interaction of aluminum metal powder, in particular with the presence of homogeneously distributed nanoscale silicon dioxide (SiO2) particles in the concrete composition, and with a sufficient proportion of carbon black, graphite or a mixture thereof as fine-grained carbon carrier distributed as homogeneously as possible in the concrete composition.
[0036] These high-strength ceramic phases, which are formed in situ when the concrete composition is fired at a temperature of about 800° C., and which contain or are one or more oxides, carbides, mixed carbides, oxycarbides, nitrides and / or oxynitrides, and / or their respective mixtures, are in the fired concrete component in a structure that is advantageously small-scale on the micrometer and / or nanometer scale and are therefore distributed approximately uniformly in the fired concrete component. Thus, with the concrete composition according to the invention, it is possible to produce fired concrete components that have strength properties that are as uniform as possible, thanks to the uniformly distributed ceramic phases, and these components are particularly dimensionally stable.
[0037] It is particularly advantageous if the proportion of fine-grained aluminum metal powder in the concrete composition according to the invention is adjusted to 3% by weight to 6% by weight, so that a sufficient proportion of such new aluminum-based ceramic phases is formed and distributed in the fired concrete product produced from the concrete composition according to the invention. Preliminary tests have shown that, for example, by selecting a proportion of 5% by weight of fine-grained aluminum metal powder in the concrete composition, the strength of the fired concrete component produced thereby can be further increased, because the proportion of aluminum-based ceramic phases or structures formed in situ in the fired concrete component is further increased. From the current point of view, especially for economic reasons, having a proportion of 5% by weight of fine-grained aluminum metal powder in the concrete composition seems to achieve the best cost-benefit ratio. In the case of further increasing the proportion of aluminum metal powder in the concrete composition according to the invention up to about 7% by weight, the above-mentioned technical advantages are still increased, but the material costs for producing the concrete composition according to the invention are also increased.
[0038] In the refractory concrete composition, the total proportion of the at least one refractory raw material or the refractory raw material mixture amounts to 65 to 90% by weight. This particle size distribution of the at least one refractory raw material or the raw material mixture is provided by a proportion of 35 to 70% by weight of a coarse-grained fraction having a particle size of at least 0.5 mm and by a proportion of 15 to 30% by weight of a fine-grained fraction having a particle size of less than 0.5 mm. In this case, the granular coarse components having a particle size of at least 0.5 mm are advantageously embedded in a bonding matrix formed by the fine-grained fraction of the at least one refractory raw material and the proportion of other fine-grained components having a particle size of less than 0.5 mm in the refractory concrete composition.
[0039] Soot, carbon black, shiny soot, amorphous graphite and mixtures thereof can be used as fine-grained carbon supports. The term "carbon black" refers to a type of soot produced specifically as an industrial raw material. Shiny soot is soot produced by combustion equipment.
[0040] In the concrete composition, fine-grained magnesium oxide powder (MgO) in a possible proportion of 0 to 2% by weight is used as a setting accelerator to shorten the setting time during the production of refractory concrete. Depending on the fineness of the material, the refractory concrete composition according to the present invention only needs to contain a very small proportion of magnesium oxide powder, for example about 0.05% by weight, which is sufficient to achieve a relatively fast setting time of the refractory concrete.
[0041] In a preferred embodiment of the invention, it can be particularly useful if the solid content of amorphous nanoscale silica particles in the concrete composition is 2 to 7% by weight. This ratio corresponds to the dry anhydrous solid content of the silica particles contained in the provided aqueous colloidal silica sol suspension. Thus, sufficient but not excessive reactive silica (SiO2) is provided in order to achieve in situ formation of a favorable ceramic phase in a corresponding amount in the fired concrete component produced according to the invention.
[0042] When the amorphous nanoscale silicon dioxide particles have a particle size of 2 nm to 100 nm, preferably a particle size of 5 nm to 75 nm, the refractory concrete composition according to the invention can achieve a particularly high reactivity during the subsequent firing, in particular for the new phase formation of the desired ceramic phase. The correspondingly high reactivity ensured by the correspondingly small particle size allows rapid phase formation even at low temperatures.
[0043] Compared to the concrete composition according to the invention, amorphous silica powder, for example, with a particle size in the micrometer (μm) range, does not show sufficient reactivity, which is why when such a mixture is subsequently fired, advantageous ceramic phases in such a microstructure cannot be obtained with silica powder particles in the micrometer range.
[0044] In order to provide a refractory concrete composition according to the invention which can be used as flexibly as possible for different applications, at least one refractory raw material is selected from the group consisting of sintered aluminum oxide, fine corundum, brown corundum, gray corundum, magnesia-aluminum spinel, mullite, bauxite, andalusite, refractory clay and / or silicon carbide, and mixtures thereof.
[0045] Fireclay is a rock-like, man-made refractory material with a proportion of 10 to 45% alumina (Al2O3). Fireclay does not refer to other refractory building materials.
[0046] Depending on the field of application and on the specific requirements placed on the refractory product, different refractory raw materials or raw material mixtures can be used. For example, relatively higher quality refractory raw materials such as sintered alumina, fine corundum or magnesia alumina spinel or mixtures thereof can be used for highly stressed refractory products and in particular for refractory products that are subject to high thermal and / or mechanical stresses such as those required in steel production processes.
[0047] In other application areas, if the refractory products are subjected to less stress and are not in direct contact with steel and slag, relatively more cost-effective refractory raw materials such as bauxite, andalusite and refractory clay can be used, for example, which have more advantages in terms of cost performance compared to the above-mentioned high-quality refractory raw materials.
[0048] If amorphous nanoscale silica particles and / or at least one fine-grained carbon support and / or fine-grained aluminum metal powder are uniformly distributed in the concrete composition for producing the concrete component, it can be particularly advantageous for the in-situ new phase formation of the desired ceramic phase in the fired concrete component. The uniform distribution of these fine-grained components, especially the nanoscale silica particles, ensures that the ceramic phase newly formed in situ during the firing of the refractory concrete composition is uniformly distributed in the fired concrete material. As a result, material properties that are as uniform as possible can be achieved in all aspects of the fired concrete material produced according to the invention.
[0049] To ensure the most uniform or homogeneous distribution of one or more of said fine-grained ingredients in the concrete composition, the dry starting materials for producing the refractory concrete composition may conveniently be dry-mixed in a suitable concrete mixer or pugmill mixer even before adding the silica sol as a mixing fluid. Additionally or alternatively, the dry mix for preparing the refractory concrete composition may then be mixed during the addition of a corresponding amount of an aqueous colloidal silica sol suspension to ensure a homogeneous distribution of one or more of said fine-grained ingredients in the concrete composition.
[0050] In an alternative embodiment of the invention, the refractory concrete composition may be free of setting accelerators, in particular free of magnesium oxide. As mentioned above, the magnesium oxide optionally added to the concrete composition acts as a setting accelerator. However, the concrete composition according to the invention can also be prepared or processed without magnesium oxide. If necessary, it is possible to operate without adding a setting accelerator. Alternatively, for example, lime, Portland cement, calcium aluminate cement, magnesium chloride and / or other magnesium salts, alone or in a mixture, can be used as a setting accelerator instead of magnesium oxide.
[0051] However, the addition of the at least one setting accelerator can reduce the refractory properties, thereby reducing the application limit temperature of the refractory concrete composition according to the present invention. The setting accelerator is an alkaline component, while the refractory raw materials of the refractory concrete composition according to the present invention are non-alkaline. This combination can lead to the formation of a low melting point phase at high temperatures. Therefore, reducing or completely eliminating the use of the setting accelerator in the refractory concrete composition can have advantages in terms of application technology.
[0052] From a technical point of view, it is in principle possible to use a higher proportion of basic refractory raw materials such as magnesium oxide (MgO) or dolomite in the refractory raw material mixture. However, this results in a higher proportion of basic refractory raw materials in the concrete composition, as the sol-gel reaction proceeds faster, especially if these are fine-grained. In this case, the concrete composition will solidify particularly quickly, thereby shortening the processing time of the concrete composition for casting concrete elements. However, such concrete elements exhibit poorer hot strength properties due to the low-melting phases that appear when the temperature rises or the alkaline oxides (e.g. MgO, CaO) and non-alkaline oxides (e.g. SiO2, Al2O3) that are common in the microstructure are fired.
[0053] In a further development of the refractory concrete composition according to the invention, the concrete composition may further comprise at least one dispersant, wherein the at least one dispersant preferably comprises or is sodium polynaphthalene sulfonate. By adding a suitable dispersant, the fluidity of the concrete may be improved, thereby enabling the required amount of mixing fluid to be added, in this case the required amount of aqueous colloidal silica sol suspension, to be reduced. In particular, in the case of carbonaceous concrete, the addition of a suitable dispersant may be particularly advantageous, since carbon is generally poorly wetted by water.
[0054] The above-mentioned objects of the present invention are also achieved by casting a concrete component produced by casting a refractory concrete composition according to any one of claims 1 to 7. As mentioned above, the microstructure of the concrete component according to the present invention still contains the above-mentioned proportions of fine-grained aluminum metal powder (Al), fine-grained carbon carrier (C) and nano-scale silicon dioxide (SiO2) particles. Advantageously, the fine-grained or nano-scale components are available as reactants for the formation of new phases in the subsequent firing, which are distributed as uniformly as possible in the microstructure. The concrete composition provided according to the present invention is flowable due to the addition of a certain proportion of aqueous colloidal silica sol suspension.
[0055] In order to ensure the most uniform distribution of the silica sol suspension as mixing fluid in the concrete composition, it may be advantageous if the provided refractory concrete composition is appropriately mixed before the concrete element is cast into the formwork mold. This ensures that the fine-grained components required for forming the ceramic phase in the fired concrete material, in particular the aluminum powder, the nano-scale silica particles and the carbon support material, are also distributed as uniformly as possible in the microstructure of the concrete element.
[0056] Refractory concrete components and building elements offer convenience to the end customer, as the necessary, sometimes time-consuming and complex production steps have already been carried out in advance.
[0057] This may be particularly advantageous or necessary if the concrete element produced with the refractory concrete composition according to the invention is substantially free of water.
[0058] Such a concrete element can be produced by casting and drying a concrete composition according to any one of claims 1 to 7, or by drying a concrete element according to the invention according to claim 8. Advantageously, the drying temperature is selected in the range of 110° C. to 350° C. in order to dry or remove water substantially introduced into the concrete composition with the aqueous silica sol suspension.
[0059] In addition to being a binder and a source of reactive nanoscale amorphous silica, silica sol also has advantages in this regard. In the sol-gel process that occurs according to the reaction, which essentially leads to the green bonding of the refractory concrete, the amount of chemically bound hydrate phases produced is extremely small, and in addition, the gel structure has a higher permeability compared to other bonding systems. As a result, the drying process can be carried out very quickly and briefly at relatively low temperatures, which reduces economic and energy consumption.
[0060] The above-mentioned object of the present invention is also achieved by a fired concrete component, wherein the fired concrete component is made of the refractory concrete composition according to the present invention, and wherein the concrete component is fired at a firing temperature of 800° C. to 1600° C. and has at least one or more ceramic phases having a needle-shaped structure.
[0061] The special morphology of the ceramic phase formed in situ provides a ceramic reinforced concrete. Tensions in the fired concrete component caused by volume changes due to rapid temperature changes can therefore be absorbed more easily. This can be seen by the significantly improved thermal shock resistance of the fired concrete component produced according to the invention. Under frequent temperature changes, the fired concrete material shows significantly better durability than traditional refractory materials. In addition to their high mechanical strength, the ceramic phase formed in situ is also extremely resistant to chemical attack (such as contact with liquid slag).
[0062] Compared to the method of CN 110 240 486B, the fired concrete components produced according to the invention do not form in-situ formed mullite whiskers, since there are no ceramic microcapsules in the refractory concrete composition.
[0063] In order to ensure that the ceramic phase formed as a ceramic reinforcement is distributed as evenly as possible throughout the microstructure of the fired concrete component, it may be expedient to fire the concrete component for a sufficiently long period of time at the selected firing temperature to ensure the most uniform temperature distribution during the firing process and the temperature gradient within the concrete component is as small as possible. In order to make the temperature distribution within the concrete component as uniform as possible during the firing process, the required firing time depends to a large extent on the size and geometry of the concrete component to be fired, in particular the wall thickness. The relevant test standards for dense refractory products should specify the firing temperature and the holding time required to fully heat the test specimen to the specified firing temperature. For example, the holding time of 5 hours specified in the DIN EN 993-10 standard (in the case of testing according to DIN EN 993-10 at 1700°C) for determining the permanent change in the length of dense shaped refractory products can be used as a guideline for the firing time at the selected firing temperature.
[0064] Particularly advantageous material properties may result for the fired concrete component according to the invention if at least one ceramic phase contains or is aluminum in the form of one or more oxides, carbides, mixed carbides, oxycarbides, nitrides and / or oxynitrides and / or mixtures thereof.
[0065] Surprisingly, it has been found that at least one or more ceramic phases are preferably formed when the concrete product is pretreated and / or fired at a firing temperature in the range of 800° C. to 1600° C., preferably at a firing temperature of at least 1000° C., particularly preferably at a firing temperature of at least 1250° C.
[0066] In the following Table 1, an overview of the ceramic phases or phase groups formed in situ, which are formed during the temperature pretreatment of the dry concrete components produced according to the invention (see Table 1, left column) at the minimum temperature specified in each case, and which can in turn transform into other phases when the temperature is further increased. The ceramic phases or phase groups formed are extremely stable both mechanically and chemically and partly have an acicular structure. The refractory concrete produced according to the invention containing such ceramic phases or phase groups therefore has the advantages of ceramic reinforcement and has extremely good strength, high thermal shock resistance and high chemical stability to aggressive media such as liquid slag when the temperature changes.
[0067] A dry concrete component produced with the refractory concrete composition according to the invention and suitably dried at a drying temperature of 110° C. to 350° C. contains in its microstructure, among other substances, fine-grained and uniformly distributed aluminum metal powder (Al), fine-grained and uniformly distributed carbon support material (C) and nanoscale silicon dioxide (SiO2) particles in proportions required for the formation of new phases during subsequent firing. Such a dry refractory concrete component can already be delivered to the customer.
[0068] In detail, in the fired concrete component produced according to the present invention, at a firing temperature of at least 700° C., new phase formation is determined, which comprises, for example, aluminum oxide in the form of Al 2 O 3 , aluminum carbide in the form of Al 4 C 3 and silicon (Si).
[0069] After raising the temperature of the tested concrete component to a firing temperature of at least 800° C., new phases can be determined at 800° C., which include, for example, aluminum oxide (Al 2 O 3 ), silicon (Si), aluminum carbide (Al 4 C 3 ) and aluminum silicon (Al—Si) mixed carbides.
[0070] After the temperature of the tested concrete component was further increased to a firing temperature of at least 1300° C., new phases were observed to form at 1300° C., which phases included, for example, aluminum oxide (Al2O3), aluminum carbide (Al4C3), aluminum nitride (AlN), aluminum oxycarbide and Al—Si mixed carbides. Aluminum carbide decomposes at higher temperatures from 1300° C. and forms Al—Si mixed carbides.
[0071] When the temperature is further increased to a firing temperature of at least 1600° C., in the tested concrete components according to the invention, the formation of new phases can be determined at 1600° C., which phases include, for example, aluminum oxide (Al 2 O 3 ), aluminum nitride (AlN), aluminum oxynitride (AlON), aluminum oxycarbonitride (AlCON) and silicon aluminum oxynitride (SiAlON) ceramic phases.
[0072]
[0073] Table 1: In-situ new phase (phase group) formation in the concrete material according to the invention at different firing temperatures (700° C. to 1600° C.)
[0074] The newly formed phase structures not only show excellent mechanical resistance, but they are also very stable in their chemical properties and are particularly resistant to slag attack, i.e. chemically resistant to contact with liquid slag. This circumstance, combined with the very good penetration resistance due to the special pore size distribution, leads to an extremely good slag resistance to various slags, which frequently come into contact with the refractory material during steel production. Compared with conventional and known materials, the open pores of the refractory concrete according to the invention show significantly smaller void sizes, so that in contact with liquid phases such as aggressive slag, significantly lower capillary forces occur, and penetration of the fired concrete material according to the invention by these media does not occur or occurs only to a small extent compared with previously known refractory materials. This circumstance significantly increases the slag resistance of the fired concrete components produced according to the invention.
[0075] A further technical advantage of the fired concrete elements produced according to the invention, which is particularly prominent in most steel production applications, is that the thermal conductivity of the concrete elements produced from the refractory concrete composition according to the invention is relatively low compared to conventional carbon-bound materials. This can be explained by the relatively low carbon content in the concrete composition according to the invention. At an ambient temperature of 1000° C., the thermal conductivity of the fired concrete elements produced according to the invention is, for example, about 4 W / mK, whereas the thermal conductivity of conventional isostatically pressed products used in continuous casting processes is, for example, greater than 10 W / mK. Thus, heat losses can be significantly reduced with the concrete elements produced according to the invention.
[0076] In our own preliminary tests, it was surprisingly found that fired concrete components produced according to the invention can have a cold compressive strength (according to DIN EN 993-5) of at least 140 MPa, preferably at least 160 MPa, and / or a cold flexural strength (according to DIN EN 993-6) of at least 20 MPa after pretreatment at a firing temperature of at least 1000° C. These very high values are caused by the extremely mechanically stable and sometimes needle-like or acicular structure of the newly formed phases.
[0077] Furthermore, preliminary tests have shown that concrete elements produced according to the invention can have a hot flexural strength of at least 15 MPa (according to ISO 5013 or DIN EN 993-7, respectively) measured at 1500° C. Such a high hot flexural strength indicates that the material has an extraordinary mechanical stability at high temperatures.
[0078] The fired concrete components produced according to the invention can be used in a particularly flexible manner if the fired concrete components are substantially volume stable and if the length of the fired concrete components after cooling (determined in accordance with DIN EN 993-10) changes permanently by -0.1% to +0.1% relative to their initial length before firing. This geometric stability of the concrete material according to the invention has great advantages both at very high firing temperatures and after firing at very high temperatures, for example with regard to the stability and service life of the refractory lining.
[0079] The above-mentioned object of the present invention is also achieved by a method for producing a fired concrete component according to the present invention, wherein the method comprises the following steps:
[0080] - providing a refractory concrete composition according to the present invention;
[0081] - casting the refractory concrete composition into a formwork mould, wherein the concrete composition sets into a concrete element;
[0082] - removing the concrete element from the formwork mould;
[0083] - optionally, drying the concrete element, preferably wherein a drying temperature of 110° C. to 350° C. is selected for drying;
[0084] The concrete component is fired at a firing temperature of 800° C. to 1600° C., preferably at a firing temperature of at least 1000° C., particularly preferably at a firing temperature of at least 1250° C.
[0085] In the context of the production method according to the invention, mixing of the components of the refractory concrete composition may be additionally optionally required before providing the refractory concrete composition. For example, it may be convenient to initially mix the dry starting material for producing the refractory concrete composition with a corresponding amount of an aqueous colloidal silica sol suspension and to mix uniformly in a suitable agitator. In this case, the dry starting material and the aqueous colloidal silica sol suspension can advantageously be stored separately from one another. When the dry starting material is mixed with the aqueous colloidal silica sol suspension as a mixing fluid, the amount and weight proportion of the components to be mixed can advantageously be precisely controlled and adjusted. In this way, the amount of water or moisture introduced with the aqueous colloidal silica sol suspension can also be accurately adjusted, controlled and recorded, respectively.
[0086] This therefore ensures that the refractory concrete composition provided by the formulation according to the invention is flowable and also contains water or moisture, respectively, in the corresponding desired proportions.
[0087] The provided refractory concrete composition is then cast into a suitable formwork mold as a flowable material. Advantageously, the casting can be carried out under shaking and / or vibration of the corresponding formwork mold to compact the cast concrete composition in the formwork mold by the applied vibration energy. For example, several prepared formwork molds can be placed on a vibration table and thus several concrete elements can be produced simultaneously. After the concrete has solidified, the concrete element is removed from the formwork mold or the formwork mold is removed accordingly, thereby obtaining a solidified concrete element.
[0088] In an appropriate and optional manner, the concrete element or the profiled body is subsequently dried in a suitable drying unit, preferably at a temperature of 110° C. to 350° C.
[0089] The advantages of subjecting the concrete components according to the invention to a final firing temperature of at least 800° C. have already been pointed out. These high-strength ceramic phases formed in situ during the firing of the concrete composition at a temperature of about 800° C., and in the form of one or more oxides, carbides, mixed carbides, oxycarbides, nitrides and / or oxynitrides, and / or their respective mixtures, are advantageously small-scale structures on the micrometer and / or nanometer scale in the fired concrete component and are therefore distributed approximately uniformly in the fired concrete component. Thus, with the concrete composition according to the invention, it is possible to produce fired concrete components having strength properties that are as uniform as possible, which, due to the uniformly distributed ceramic phases, are particularly dimensionally stable. BRIEF DESCRIPTION OF THE DRAWINGS
[0090] Figure 1 The course of the cold compressive strength (measured in accordance with DIN EN 993-5) of a concrete material produced according to the invention as a function of the pretreatment temperature is shown.
[0091] At pretreatment temperatures between 700°C and 800°C, there is a sudden increase in the measured cold compressive strength (expressed in MPa), which is Figure 1 This is evident in Table 2, because during the firing process of the fired concrete member according to the invention, in-situ new phase formation occurs at a pretreatment temperature of 700° C. For this purpose, concrete members made from the concrete composition according to the invention were tested. The formulation specifications of the concrete composition according to the invention used for the strength test correspond to the values given in Table 2 for exemplary embodiments 2 and 3.
[0092] The mechanically extremely stable ceramic phases formed in situ during firing, partly with an acicular structure, give the refractory concrete material according to the invention an extremely high mechanical stability and strength over a very wide temperature range of 700° C. to 1600° C. and above. In the temperature range of 800° C. to 1300° C., a cold compressive strength of at least 140 MPa was measured. At a pretreatment temperature of 1000° C., even a cold compressive strength of 160 MPa could be determined for the fired concrete elements produced according to the invention.
[0093] Mode for Carrying Out the Invention
[0094] Table 2 below lists some exemplary embodiments according to the present invention in the form of possible formulations for producing refractory concrete compositions.
[0095] Exemplary embodiments 1 to 5 of the refractory concrete composition according to the invention detailed in Table 2 are used for the subsequent production of refractory concrete components, which can be used by the customer after appropriate drying. Usually, the dried concrete components are first fired on site at the customer's premises in order to have the advantages mentioned above as fired refractory concrete components.
[0096] The formulations of the refractory concrete compositions according to exemplary embodiments 1, 4 and 5 listed in Table 2 are generally used in application scenarios where the refractory concrete materials produced therefrom come into contact with pig iron. For example, in pig iron production, there are refractory applications of refractory concrete components in the fields of pig iron ladles, blast furnace gussets and / or torpedo ladles.
[0097] The refractory concrete compositions according to exemplary embodiments 2 and 3 in Table 2 are generally used for steel production applications, i.e., for example, for refractory concrete blocks in the field of ladles, ladle bottoms, ladle walls, for perforated blocks, and for various functional refractory products required in continuous casting processes. Figure 1 The values of cold compressive strength (in MPa) shown in Table 2 are measured based on fired concrete members made from the refractory concrete compositions according to exemplary embodiments 2 and 3 in Table 2. Other specified strength values (cold flexural strength, hot flexural strength) are also measured based on these refractory concrete compositions according to exemplary embodiments 2 and 3 in Table 2.
[0098]
[0099]
[0100] Table 2: Formulation of Refractory Concrete Composition According to the Present Invention (Exemplary Embodiments 1 to 5)
[0101] In order to provide a refractory concrete composition according to the invention, in the formulations according to exemplary embodiments 1 to 5, a dry mixture of the raw material components was first prepared in a homogeneous manner without silica sol as a mixing fluid. For this purpose, the prepared dry mixture was homogeneously mixed according to the respective formulation. Subsequently, the dry mixture was mixed with an aqueous colloidal silica sol suspension in the amount detailed in Table 2, wherein in each case a silica sol suspension having a solids content of 40% by weight of amorphous nanoscale silicon dioxide particles (based on the silica sol suspension) was provided.
[0102] The dry mixture of the raw material components and the silica sol suspension are uniformly mixed in a paddle stirrer for 3 to 5 minutes each time.
[0103] Thus, the refractory concrete composition according to the invention is provided to be flowable and can then be cast into a suitable formwork mold. During the casting of the refractory concrete composition, the formwork mold is advantageously vibrated in order to compact the casting material accordingly and obtain a refractory concrete component without pores as much as possible. After the concrete has been in the formwork mold for a corresponding retention time, until the setting and curing reaction of the binder (silica sol) has been completed, the produced concrete component can be removed from the formwork mold. Subsequently, drying is carried out, for example at 200° C., to obtain a refractory concrete component according to the invention. After the refractory concrete component is fired at a firing temperature of 800° C. to 1600° C., a fired concrete component prepared from one of the concrete compositions according to the invention described in detail in exemplary embodiments 1 to 5 can be obtained.
Claims
1. A refractory concrete composition comprising: a coarse-grained fraction of at least one refractory raw material having a grain size of at least 0.5 mm, preferably having a grain size of 0.5 mm to 12 mm, in a proportion of 35 to 70%, preferably 50 to 65%, by weight; - a fine-grained fraction of the at least one refractory raw material having a grain size of less than 0.5 mm in a proportion of 15 to 30%, preferably 20 to 25%, by weight; - wherein the at least one refractory raw material is selected from the group consisting of sintered alumina, fine corundum, brown corundum, grey corundum, magnesia alumina spinel, mullite, bauxite, andalusite, refractory clay and / or silicon carbide and mixtures thereof; - fine-grained calcined aluminum oxide having a particle size of less than 0.1 mm, preferably having a particle size of less than 50 μm, in a proportion of 0 to 20%, preferably 1 to 7%, by weight; - fine-grained magnesium oxide powder having a particle size of less than 0.1 mm in a proportion of 0 to 2% by weight; - a fine-grained aluminum metal powder having a particle size of less than 100 μm, preferably having a particle size of less than 63 μm, in a proportion of 2 to 7%, preferably 3 to 6%, by weight; - a proportion of 2 to 8% by weight of at least one fine-grained carbon support having a particle size of less than 100 μm, wherein the at least one fine-grained carbon support comprises or is carbon black and / or graphite; - an aqueous colloidal silica sol suspension in a proportion of 4 to 20% by weight, wherein the silica sol suspension comprises amorphous nanoscale silica particles having a solid content of 30 to 50% by weight.
2. The refractory concrete composition according to claim 1, characterized in that The solid content of amorphous nano-sized silica particles in the concrete composition is 2 to 7% by weight.
3. The refractory concrete composition according to claim 1 or 2, characterized in that: The amorphous nano-sized silica particles have a particle size of 2 nm to 100 nm, preferably 5 nm to 75 nm.
4. The refractory concrete composition according to any one of claims 1 to 3, characterized in that The total proportion of the at least one refractory raw material or the refractory raw material mixture in the concrete composition amounts to 65 to 90% by weight.
5. The refractory concrete composition according to any one of claims 1 to 4, characterized in that After mixing the ingredients of the refractory concrete composition, the amorphous nano-sized silica particles and / or the at least one fine-grained carbon support and / or the fine-grained aluminum metal powder are uniformly distributed in the concrete composition.
6. The refractory concrete composition according to any one of claims 1 to 5, characterized in that The concrete composition contains no accelerators and in particular no magnesium oxide.
7. The refractory concrete composition according to any one of claims 1 to 6, characterized in that The concrete composition further comprises at least one dispersant, wherein the at least one dispersant preferably comprises or is sodium polynaphthalene sulfonate.
8. A concrete member produced by casting the refractory concrete composition according to any one of claims 1 to 7, characterized in that The microstructure of the concrete member includes fine-grained aluminum metal powder, fine-grained carbon support, and nano-sized silica particles in the proportions proposed in the concrete composition.
9. The concrete component according to claim 8, characterized in that The concrete element contains no water, in particular after drying at a drying temperature of 110° C. to 350° C.
10. A fired concrete member produced from the refractory concrete composition according to any one of claims 1 to 7, characterized in that The fired concrete member is fired at a firing temperature of 800° C. to 1600° C. and has at least one or more ceramic phases having a needle-like structure.
11. The fired concrete component according to claim 10, characterized in that: The at least one ceramic phase comprises aluminum in the form of one or several oxides, carbides, mixed carbides, oxycarbides, nitrides and / or oxynitrides and / or mixtures thereof.
12. The fired concrete component according to claim 10 or 11, characterized in that: After pretreatment at a firing temperature of at least 1000° C., the fired concrete component has a cold compressive strength according to DIN EN 993-5 of at least 140 MPa, preferably at least 160 MPa, and / or a cold flexural strength according to DIN EN 0993-6 of at least 20 MPa.
13. The fired concrete component according to any one of claims 10 to 12, characterized in that: The fired concrete component has a hot flexural strength of at least 15 MPa, measured at 1500° C. in accordance with ISO 5013 and DIN EN 993-7, respectively.
14. The fired concrete component according to any one of claims 10 to 13, characterized in that The volume of the fired concrete component is essentially stable and, according to DIN EN 993-10, after cooling has a permanent change in length of -0.1% to +0.1% relative to its initial length before firing.
15. A method for producing a fired concrete component according to any one of claims 10 to 14, comprising the following steps: - Providing a refractory concrete composition according to any one of claims 1 to 7; - casting the refractory concrete composition into a formwork mould, wherein the concrete composition sets into a concrete element; - removing the concrete element from the formwork mould; - optionally, drying the concrete element, preferably wherein a drying temperature of 110° C. to 350° C. is selected for drying; The concrete component is fired at a firing temperature of 800° C. to 1600° C., preferably at a firing temperature of at least 1000° C., particularly preferably at a firing temperature of at least 1250° C.
Citation Information
Patent Citations
A whisker-reinforced Al2O3-SiC-C iron trench castable and its preparation method
CN110240486B
Castable refractory for trough of blast furnace
JP2001114571A
Refractory composition for the steel industry
KR101047358B1
Cement-free refractory
US20120142518A1
Castable refractory composition
US20140291904A1